The inward rectifier current inhibitor PA‐6 terminates atrial fibrillation and does not cause ventricular arrhythmias in goat and dog models. (28th June 2017) - Ji, Yuan; Varkevisser, Rosanne; Opacic, Dragan; Bossu, Alexandre; Kuiper, Marion; Beekman, Jet D M; Yang, Sihyung; Khan, Azinwi Phina; Dobrev, Dobromir; Voigt, Niels; Wang, Michael Zhuo; Verheule, Sander; et al.
Abstract : Background and Purpose: The density of the inward rectifier current (IK1 ) increases in atrial fibrillation (AF), shortening effective refractory period and thus promoting atrial re‐entry. The synthetic compound pentamidine analogue 6 (PA‐6) is a selective and potent IK1 inhibitor. We tested PA‐6 for anti‐AF efficacy and potential proarrhythmia, using established models in large animals. Experimental Approach: PA‐6 was applied i.v. in anaesthetized goats with rapid pacing‐induced AF and anaesthetized dogs with chronic atrio‐ventricular (AV) block. Electrophysiological and pharmacological parameters were determined. Key Results: PA‐6 (2.5 mg·kg −1 ·10 min −1 ) induced cardioversion to sinus rhythm (SR) in 5/6 goats and prolonged AF cycle length. AF complexity decreased significantly before cardioversion. PA‐6 accumulated in cardiac tissue with ratios between skeletal muscle : atrial muscle : ventricular muscle of approximately 1:8:21. In SR dogs, PA‐6 peak plasma levels 10 min post infusion were 5.5 ± 0.9 μM, PA‐6 did not induce significant prolongation of QTc and did not affect heart rate, PQ or QRS duration. In dogs with chronic AV block, PA‐6 did not affect QRS but lengthened QTc during the experiment, but not chronically. PA‐6 did not induce TdP arrhythmias in nine animals (0/9) in contrast to dofetilide (5/9). PA‐6 (200 nM) inhibited IK1, but not IK, ACh, in human isolated atrial cardiomyocytes. Conclusion and Implications: PA‐6 restored SR in goats with persistent AF and, in dogs with chronic AV block, prolonged QT intervals, without inducing TdP arrhythmias. Our results demonstrate cardiac safety and good anti‐AF properties for PA‐6.